PEMBERIAN PENGUATAN OLEH GURU PEMBIMBING TERHADAP PESERTA DIDIK DALAM LAYANAN INFORMASI DI SMP NEGERI 26 PADANG - Efendi, Ismi Auldra; Arief, Asmaiwaty; Nofrita, Nofrita (Bimbingan dan Konseling, 2013)
Based on observation that have done by writer, there are many students who got less responses or reinforcement in information service : how the guider teacher give reinforcement to students in information services at Junior High School Number 26 Padang, perceived from : 1). Gift the verbal reinforcement by the guider teacher in information services activity at Junior High School Number 26 Padang and 2). Gift the non verbal reinforcement by the guider teacher in information services activity at Junior High School Number 26 Padang. This research is descriptive research which is trying to describe the real condition of subject. Population of this research all of students class VIII and IX Junior High School Number 26 Padang at 2011-2012 education period, amount of population is 236 people. Sample of this research is chose based on purposive technique sampling which sample is suitable to research. Amount of Samples in this research are 56 students. Colecting of data by using quistionnaire. Annalisis that used is descriptive statistic which using formulation of persentation. The result of research showing : 1). The Verbal Reinforcement by guider teacher in information services activity include to good enough and 2). The Non Verbal Reinforcement by the guider teacher in non verbal reinforcement by the guider teacher in information services activity include to good enough. Based on the result of research above, the researcher can seen if gift the reinforcement by the guider teacher to students in information services activity at Junior High School Number 26 Padang is good enough. The researcher is advising to the teacher in order to increase the reinforcement to the students in informaton services.